The Syntax Distance of Turkish and Its Applied Aspects - Uzun, Cemile (Taylor and Francis, 2026)
This book offers a comprehensive examination of the syntactic structures of Turkish across its historical periods, from Old Turkish to Chagatai Turkish. Moving beyond traditional descriptive approaches, it applies dependency grammar and quantitative methods to reveal structural variation and diachronic change. Drawing on carefully prepared corpora representing seven key stages of Turkish, the analysis addresses measures such as syntactic distance, nucleus–actant relations, bridge–node ratios, and structural centrality. Through computational models and natural language processing tools, it provides a systematic profile of how Turkish sentence structures have evolved over time. This perspective highlights not only formal and functional aspects but also the communicative and narrative needs that shaped expression in different periods. The book sheds light on the formal and functional dimensions of Turkish syntax and builds a bridge between theoretical linguistics and the digital humanities. By introducing the GSM-4 model, it offers a reproducible framework for measuring syntactic complexity in historical texts. In this respect, the volume serves as an important resource not only for Turkologists and historical linguists but also for researchers in computational linguistics, language typology, and cognitive linguistics. © 2027 Cemile Uzun. All rights reserved.
Keywords: Bridges; Computational Linguistics; Natural Language Processing Systems; Comprehensive Examination; Computational Modelling; Dependency Grammar; Historical Periods; Model Languages; Natural Language Processing Tools; Quantitative Method; Structural Variations; Syntactic Structure; Turkishs; Syntactics